2012
DOI: 10.1590/s0100-736x2012001100007
|View full text |Cite
|
Sign up to set email alerts
|

Suscetibilidade a desinfetantes e perfil de resistência a antimicrobianos em isolados de Escherichia coli

Abstract: RESUMO.-A colibacilose, causada por Escherichia coli, é a enfermidade entérica de maior impacto na produção de suínos, podendo levar à morte do animal. Esta bactéria possui grande capacidade de desenvolver resistência a múltiplos antimicrobianos e a desinfetantes. Desta forma, estudos que abordem mecanismos de resistência e perϐil de amostras de campo tornam-se necessários. E. coli é amplamente utilizada como modelo de estudos que exploram a resistência intrín-seca e extrínseca a multidrogas. Neste trabalho, b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
3
0
3

Year Published

2016
2016
2022
2022

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 26 publications
1
3
0
3
Order By: Relevance
“…This was observed in the present study, in which 99.21% (125/126) of the strains exhibited multiresistance, which is a similar result to that obtained by Krewer et al (2012), who reported that this result could indicate the potential for horizontal transfer of resistance genes. Mota et al (2005) reported that high rates of multiple resistance to antimicrobials represent a great risk to public health by hindering the treatment of animal and human diseases.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…This was observed in the present study, in which 99.21% (125/126) of the strains exhibited multiresistance, which is a similar result to that obtained by Krewer et al (2012), who reported that this result could indicate the potential for horizontal transfer of resistance genes. Mota et al (2005) reported that high rates of multiple resistance to antimicrobials represent a great risk to public health by hindering the treatment of animal and human diseases.…”
Section: Discussionsupporting
confidence: 92%
“…Baccaro et al (2002) recorded 97% of strains resistant to this antimicrobial when analyzing 600 E. coli isolates from piglets with diarrhea in the state of São Paulo. Ten years later, Krewer et al (2012) analyzed 62 isolates of E. coli from the feces of pigs in the south of Brazil and found that 16.3% of the samples were resistant to this active ingredient. This behavior could be explained by a determination from the Ministry of Agriculture, Fishing and Supplies (Normative Instruction no.…”
Section: Discussionmentioning
confidence: 99%
“…Muitos mecanismos podem ser utilizados pela bactéria para adquirir resistência aos antimicrobianos, dentre eles temos a chamada resistência adquirida, que é a expressão de bombas de efluxo que expulsam moléculas do antibiótico do meio intracelular para o extracelular, impedindo ou dificultando sua ligação com o sitioalvo, causando, desta maneira, diminuição ou supressão da sensibilidade a múltiplos antimicrobianos ou podem ocorrer mutações em um ou mais genes que codificam regiões-alvo (proteínas) destes antimicrobianos (BAPTISTA, 2013;KREWER et. al., 2012;KAUR, 2018).…”
Section: Discussionunclassified
“…Enteritis can appear in three different stages: neonatal diarrhea appears in the first days of life; piglet diarrhea from the first week of life to weaning; and post-weaning diarrhea. E. coli is the agent most frequently associated with neonatal and post-weaning diarrhea in swine [14,15,16,17,18,19,20,21,22]. From the clinical point of view, piglets might refuse to suckle and exhibit watery diarrhea leading quickly to dehydration, weakness and eventually death [15,22,23].…”
Section: Introductionmentioning
confidence: 99%